2010
DOI: 10.1590/s1414-32832010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Adolescência e trabalho: significados, dificuldades e repercussões na saúde

Abstract: Foram investigadas experiências de trabalho de adolescentes trabalhadores e as repercussões na saúde. A pesquisa foi desenvolvida em uma escola de Fortaleza, Ceará, em 2008, com dez adolescentes trabalhadores. O estudo foi exploratório, com abordagem qualitativa, tendo o grupo focal e o diário de campo como instrumentos de coleta de dados. A análise dos dados seguiu a análise de conteúdo. Foram respeitados os aspectos legais e éticos. Com o desenvolvimento do estudo, surgiram quatro categorias: características… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…Work in adolescence, in the majority of cases, is associated with a low economic condition, since it represents one of the personal or family strategies to provide their basic needs, guaranteeing help with paying expenses or acquisition of consumer goods (6)(7) . Indeed, the results of this study showed an alarming percentage of adolescents who work, coming from families in a condition of poverty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work in adolescence, in the majority of cases, is associated with a low economic condition, since it represents one of the personal or family strategies to provide their basic needs, guaranteeing help with paying expenses or acquisition of consumer goods (6)(7) . Indeed, the results of this study showed an alarming percentage of adolescents who work, coming from families in a condition of poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect refers to the risks for health of the adolescent worker, who is more exposed to an overload of activities that may result in a reduction in socializing with the persons who are part of his/her social network, and cause physical and mental weariness, commonly associated with harm to health (6)(7)(8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somado a isso, a pertença ou constituição de uma família também é considerado importante para o futuro pelos jovens (Valore & Viaro, 2007). Existe ainda uma afi nidade entre o futuro profi ssional e a vontade de ser fi nanceiramente independente, visto que os jovens anseiam por reconhecimento como sujeitos de direitos, bem como por oportunidades de emancipação e autonomia, através do trabalho e do desenvolvimento profi ssional (Raitz & Petters, 2008;Torres, Paula, Ferreira, & Pinheiro 2010). Assim, a inserção no mercado de trabalho e a formação educacional são vistos como elementos fundamentais para a passagem ao mundo adulto em grande parte da população jovem no Brasil, em especial para os indivíduos que necessitam exercer uma atividade laboral e colaborar no sustento da família (Mattos & Chaves, 2010).…”
Section: Discussionunclassified
“…A transição para o mundo do trabalho durante a adolescência também tem recebido destaque na literatura psicológica brasileira (Amazarry, Thomé, Souza, & Koller, 2009;Campos & Francistini, 2003;Oliveira, Fischer, Teixeira, & Amaral, 2003;Thomé, Pereira, & Koller, 2016;Torres, Paula, Ferreira, & Pinheiro, 2010). No Brasil, desde 2005, é permitido aos adolescentes exercerem atividade laboral como aprendizes.…”
Section: Introductionunclassified